Data mining for seismic slip. Issue 1 (January 2019) - Creager, Kenneth
Seismic data during the time interval between larger earthquakes could contain information about fault displacements and potential for future failure, suggest analyses of data from laboratory and real-world slow-slip earthquakes using machine-learning techniques.